2009
DOI: 10.1016/j.ijgo.2009.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Infections caused by Acinetobacter baumannii susceptible only to polymyxin in a gynecologic oncology unit

Abstract: Large multicenter surveillance studies of hospital infections show an increasing incidence of Acinetobacter baumannii infections worldwide [1]. Colonization and infection by multidrug-resistant (MDR) microbes are increasingly common in hospitalized patients. Among such isolates, A. baumannii is a common microorganism, and is usually resistant to antimicrobials such as beta-lactams and carbapenems [2,3,4].Three cases of A. baumannii postoperative wound infections that occurred in patients who underwent operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The two clinically used polymyxins, polymyxin B and colistin (Figure 1), are lipopeptide antibiotics that are used as last-line therapy against problematic Gram-negative pathogens. [1][2][3][4][5][6] Available population pharmacokinetic and pharmacodynamic data from our group indicated that the currently recommended dosage regimens of polymyxins achieve suboptimal plasma concentrations; and that higher dosing is needed to achieve effective killing and prevent resistance. 7 Neurotoxicity is an unwanted side effect that limits effective polymyxin therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The two clinically used polymyxins, polymyxin B and colistin (Figure 1), are lipopeptide antibiotics that are used as last-line therapy against problematic Gram-negative pathogens. [1][2][3][4][5][6] Available population pharmacokinetic and pharmacodynamic data from our group indicated that the currently recommended dosage regimens of polymyxins achieve suboptimal plasma concentrations; and that higher dosing is needed to achieve effective killing and prevent resistance. 7 Neurotoxicity is an unwanted side effect that limits effective polymyxin therapy.…”
Section: Introductionmentioning
confidence: 99%